Site-specific incorporation of citrulline into proteins in mammalian cells - Santanu Mondal (Nature Portfolio, 2021)
Citrullination of arginine is crucial for several physiological processes. Here the authors report the site-specific incorporation of citrulline into proteins in mammalian cells using an engineered tRNA synthetase/tRNA pair and a photocaged-citrulline.